Exploring the Effect of Teacher Feedback on Students’ Self-Efficacy - Wang, Xinxing (Journal of Research in Vocational Education, 2025)
Teacher feedback is a critical factor influencing students self-efficacy (the belief in one ability to accomplish specific tasks). This paper, based on Bandura (Bandura) self-efficacy theory and drawing on relevant research both domestically and internationally, explores the mechanisms by which teacher feedback stimulates students self-efficacy and suggests optimization paths. The study finds that the essence of issues with teacher feedback lies in the structural contradiction between the industrial-era educational paradigm and the learning needs of the brain science era. Future reforms need to achieve three major shifts. From outcome evaluation to neurocognitive development, feedback should focus on the learning process and optimize prefrontal executive function. Only by building a feedback ecosystem that aligns with the brain learning principles can we truly unlock each student potential.